The Effect of Creativity, Welfare, Self Efficacy on Performance of UMKM in Kampung Bebek Kebonsari - Zulvita, Dinda; Andriani, Dewi; Firdaus, Vera (Jurnal Ilmiah Sumber Daya Manusia, 2025)
This study aims to analyze the influence of creativity, well-being, and self-efficacy on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Kampung Bebek, Kebonsari Village. This study uses a quantitative method involving 107 respondents with data collection using a questionnaire that calculates the attitudes and views of respondents using a Likert scale. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 3.2.8 software to test the hypothesis. The results showed that creativity, well-being, and self-efficacy have a positive and significant influence on MSME performance. Creativity not only increases efficiency but also encourages innovation and quality of work results. In addition, well-being and self-efficacy also contribute to increased performance, indicating the importance of psychological factors in the work context.